A case study of EFL students’ perceptions on the use of English songs in learning English vocabulary - Basori, Basori; Setyowati, Ika Suci Ciptaning (Journal of English Language Teaching and Learning (JETLE), 2024)
The researchers observed that the difficulty faced by students at the time was the difficulty of memorizing new vocabulary, which hindered the progress of their language skills, specifically in learning English. This study aimed to understand students’ perspectives on using English song lyrics for vocabulary mastery. Using a qualitative method where questionnaires and interviews were used as the instruments, the study found some important points related to students’ perceptions of using English songs. The study found that the use of English songs improves students’ English vocabulary mastery and pronunciation despite the challenges they face when listening to English songs. Through the challenge, students found two ways of coping with the challenges that teachers need to take into account when teaching using English songs. Some limitations and future research suggestions are also explained.